SCIENTIFIC-THEORETICAL ANALYSIS OF THE CONCEPT OF PROFESSIONAL COMMUNICATIVE COMPETENCE (TAMADDUN NURI JURNALI, 2025)
The modern educational system sets itself the task not only to give knowledge, but also to train a specialist who can successfully work in personal, social and professional activities. Therefore, a competency approach is widely used as the main criterion for the content of Education. Especially when teaching foreign languages, this approach implies the formation of communicative skills on the basis of speech activity.This article discusses the scientific-theoretical analysis of the concept of professional communicative competence.